Peran Instagram Dalam Membangun Brand Awareness CV. VERALDI Padang Pada Akun @Wedding.Veraldi_Real - Aji, Dani Mulyo; ., Defhany (CV. ITTC INDONESIA, 2024)
This research explores how CV. Veraldi Padang utilizes Instagram to strengthen the brand awareness of the @Wedding.Veraldi_Real account and overcome limitations in showcasing the uniqueness of MC services. The focus is on analyzing the social media marketing strategy used by the company. The aim is to understand the impact and effectiveness of marketing strategies in building brand image and overcoming challenges faced in the context of the Instagram platform. This research method uses a qualitative approach with a case study to deeply understand CV. Veraldi's marketing strategy through Instagram. The research location was at CV Veraldi Padang. Key and supporting informants were selected through purposive sampling. Data collection was carried out through library research, interviews, and observation. Data analysis was conducted using the Miles and Huberman model, including data reduction, data presentation, and conclusion drawing. Data validity was checked through source triangulation. This research explores CV. Veraldi's strategies and challenges in building Brand Awareness through Instagram. They focus on quality and creative content, and are responsive to the audience. Despite facing negative comments and account hacks, they remain committed to maintaining their reputation and building a loyal community of followers. With a proactive approach, CV. Veraldi managed to strengthen their brand image on the Instagram platform. The interview results show that CV. Veraldi managed to build Brand Awareness on Instagram with creative content and sharing business information. They apply social media marketing theory in building Brand Awareness. CV. Veraldi overcame obstacles with careful management of their Instagram account and a silent approach to negative comments, ensuring their uniqueness remained visible. This allowed them to face the challenges effectively.